2009
DOI: 10.1021/es8031727
|View full text |Cite
|
Sign up to set email alerts
|

Light-Source-Dependent Effects of Main Water Constituents on Photodegradation of Phenicol Antibiotics: Mechanism and Kinetics

Abstract: Thiamphenicol and florfenicol are two phenicol antibiotics commonly used in aquaculture. Photodegradation experiments on these phenicols were performed in aqueous solutions under irradiation of different light sources. We found under UV-vis irradiation (lamda >200 nm) they photodegraded the fastest in seawater, followed by pure water and freshwater, whereas under solar or simulated sunlight (lamda >290 nm), they photodegraded in freshwater only. The effects of Cl- (the dominant seawater constituent), humic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
79
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(84 citation statements)
references
References 48 publications
3
79
0
2
Order By: Relevance
“…Although HA could also enhance the photodegradation as a photosensitizer (Hassett, 2006;Vione et al, 2006;Zhan et al, 2006), the result of this experiment indicated that photosensitization might be secondary to the SPY degradation. This was corresponded with previous studies that HA could bring about light attenuation (Dimou et al, 2004(Dimou et al, , 2005Ge et al, 2009). …”
Section: Natural Organic Matter (Dom)supporting
confidence: 92%
See 3 more Smart Citations
“…Although HA could also enhance the photodegradation as a photosensitizer (Hassett, 2006;Vione et al, 2006;Zhan et al, 2006), the result of this experiment indicated that photosensitization might be secondary to the SPY degradation. This was corresponded with previous studies that HA could bring about light attenuation (Dimou et al, 2004(Dimou et al, , 2005Ge et al, 2009). …”
Section: Natural Organic Matter (Dom)supporting
confidence: 92%
“…S5 and S6. SPY could undergo three reactions on basis of the product identifications: photoinduced hydrolysis, photo-oxidation and desulfonation, which are also common reaction types for the photodecomposition of other compounds (Ge et al, 2009;Trovó et al, 2009). The photooxidation reaction mediated via 1 O 2 generated product VI, which was transformed into VII through reduction process.…”
Section: Photodegradation Mechanisms and Intermediates/products Identmentioning
confidence: 99%
See 2 more Smart Citations
“…However, many factors will affect the degradation efficiency of organic pollutants in the photo-Fenton system, including pH, temperature, and the concentrations of H 2 O 2 , Fe 2+ , Cl  , dissolved organic matter (DOM) and contaminations [27,30].…”
mentioning
confidence: 99%